Daily Encounters of Mental Illness Stigma and Individual Strategies to Reduce Stigma – Perspectives of People With Mental Illness - Ong, Wei Jie; Shahwan, Shazana; Goh, Chong Min Janrius; Tan, Gregory Tee Hng; Chong, Siow Ann; Subramaniam, Mythily (Frontiers in Psychology, 2020)
Introduction: Local qualitative evaluation of mental illness stigma experienced by people with mental illness (PMI) is currently lacking in Singapore. This study aims to employ qualitative methods to identify what are the common encounters of mental illness stigma experienced by PMI in Singapore and uncover their individual strategies and efforts to reduce mental illness stigma. Methods: This study is part of a larger research project that explores the concept of mental illness stigma among different stakeholders in Singapore. Focus group discussions (FGDs) were conducted with 42 PMI to collect qualitative data on their experience with mental illness stigma including encounters of stigma and individual strategies to reduce stigma. Inductive thematic analysis method was employed to analyze the data. Results: The 8 emerged themes associated with encountering stigma in PMI’s everyday life were categorized into 2 over-arching themes, public stigma (i.e., negative beliefs and attitudes, subjected to contemptuous treatment, social exclusion, over-scrutinizing and receiving excessive care and concern) and structural stigma (i.e., requirement to declare psychiatric condition during job interview, excluded from consideration after declaration, and requirement of medical endorsements for employment). 4 themes regarding PMI’s individual strategies to reduce stigma were also identified (i.e., non-disclosure of condition, standing up for themselves, individual efforts in raising awareness, and improving themselves and live life as per normal). Limitations: Participants may be influenced by social desirability bias due to the presence of other participants in an FGD setting. Also, those who agreed to participate in the study may possess strong views or beliefs about mental illness stigma and are therefore inherently different from those who refused to participate. Conclusions: Our findings on instances of public and structural stigma encountered by PMI in Singapore can guide policy makers with the development of future policies and strategies to reduce mental illness stigma in the Singapore society. Furthermore, our study also identified individual strategies which PMI employed to reduce mental illness stigma. However, the effectiveness of these strategies were unclear and little is known of their effect on PMI themselves. Hence, there is a need for future studies to examine these.